2021
DOI: 10.1111/jpc.15688
|View full text |Cite
|
Sign up to set email alerts
|

What do children think about doctors' communication at the Teddy Bear Hospital?

Abstract: Aim: Excellent communication is essential for health professionals working with children. Teddy Bear Hospital (TBH) is an innovative method of developing paediatric communication skills in health-care students. By exploring the child's perspective of medical students' communication at the TBH, we sought to better understand the role TBH plays in the development of the communication skills in medical students. Methods: Semi-structured interviews were conducted with 31 children, aged 3-8 years old, who were atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Jazrawy et al (2021) in a scoping review that involved 11 studies of the Teddy Bear Hospital (TBH) and medical role plays involving the teddy bears, found that they were overwhelmingly positively received and that children's level of anxiety was lowered whilst their health knowledge improved. In a further review by Moore et al (2022) it was noted that while the Teddy Bear Hospital (TBH) contributed to better communication skills by medical professionals, further training on how to listen (rather than ask questions and/or impart information) was recommended. Beyers et al (2017Beyers et al ( , 2018 explored the use of teddy bears in the development of family therapy interventions with children and their parents.…”
Section: Review Of Literature Regarding the Use Of Teddy Bears In Res...mentioning
confidence: 99%
See 2 more Smart Citations
“…Jazrawy et al (2021) in a scoping review that involved 11 studies of the Teddy Bear Hospital (TBH) and medical role plays involving the teddy bears, found that they were overwhelmingly positively received and that children's level of anxiety was lowered whilst their health knowledge improved. In a further review by Moore et al (2022) it was noted that while the Teddy Bear Hospital (TBH) contributed to better communication skills by medical professionals, further training on how to listen (rather than ask questions and/or impart information) was recommended. Beyers et al (2017Beyers et al ( , 2018 explored the use of teddy bears in the development of family therapy interventions with children and their parents.…”
Section: Review Of Literature Regarding the Use Of Teddy Bears In Res...mentioning
confidence: 99%
“…Third, the presence of the object might encourage children to engage in research processes because they identify with the object more readily than they might do with adult researchers. Fourth, children are known to derive comfort and confidence from the presence of objects (such as puppets, teddy bears and dolls), which can lower anxiety and facilitate engagement in research (Epstein et al, 2008; Moore et al, 2022).…”
Section: Review Of Literature Regarding the Use Of Teddy Bears In Res...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that regardless of the different approaches and strategies used to implement the Teddy Bear Hospital, they all ultimately share the same intent: to raise health care awareness and alleviate young children's anxiety over medical treatment while focusing on the promotion of positive healthy lifestyle. Of the 11 included studies, 2 were quasi-experimental pre/post design [13], [16], 1 scoping systematic review [17], 2 were Analysis of variance ANOVA [7], [19], 1 control group trials [8] and the remainder were qualitative research studies [11], [12], [14], [15], [18].…”
Section: Objectives and Approaches Taken In Conducting The Teddy Bear Hospitalmentioning
confidence: 99%
“…All studies portray the teddy bear hospital as an intervention of medical roleplay. They took place place between the years 2008 to 2021, where two of the studies were in Canada (Ontario and London, ON) [14], [16], two in Malaysia [17], [18], two in Israel/ Palestine [8], [11], one in Norway [12], one in Germany [13], one in the Netherlands [7] and lastly, two in Australia [15], [19] as displayed in Figure 3, which predominantly involved either medical or veterinary students or researchers that dedicated their time and effort to improve on the effectiveness of medical roleplay through The Teddy Bear Hospital.…”
Section: Objectives and Approaches Taken In Conducting The Teddy Bear Hospitalmentioning
confidence: 99%